0490 Longitudinal associations between sleep and behavior and cognition in preschoolers from five European birth-cohorts. (25th May 2022) - Guerlich, Kathrin; Cadman, Tim; Charles, Marie-Aline; Fernandez-Barres, Silvia; Guxens, Monica; Heude, Barbara; Inskip, Hazel; Julvez, Jordi; Lawlor, Deborah; Salika, Theodosia; Koletzko, Berthold; Grote, Veit; et al.
Abstract: Introduction: There has been little focus on sleep and its relation to behavior and cognition in preschool-aged children. We aimed to investigate the association between sleep duration in early preschoolers (» 3.5 years of age) and later behavioral and cognitive outcomes (» 5 years of age) in European children. Methods: We used harmonized data from five cohorts from the EU Child Cohort Network, established by the LifeCycle Project (n=16.444 children): ALSPAC and SWS from UK, EDEN and ELFE from France and INMA from Spain. Within all cohorts, total sleep duration per day and behavioral and cognitive information were reported by parents. Internalizing and externalizing behaviors were measured with the Strengths and Difficulties Questionnaire and treated as percentile scores. Verbal and non-verbal intelligence were assessed by the Wechsler Preschool and Primary Scale of Intelligence or with the McCarthy Scales of Children's Abilities depending on the cohort and treated as standardized scores. All scores were cohort specific. Associations between sleep duration during early preschool age and later behavior and/or cognition were estimated using linear regression and pooled with two-stage individual participant data meta-analysis adjusted for child, maternal and household information. Analyses were done in DataSHIELD. Results: Global mean sleep duration was 11h54 ± 1h00 per day at mean age 3.5 years but differed by country, with children from France showing longer sleep duration than children from the UK or Spain. In multivariate meta-analysis, 1 hour of additional sleep duration per day at mean age 3.5 years was associated with reduced internalizing and externalizing behavior percentile scores at mean age 5.1 years (internalizing behavior: badjusted= -1.05, 95%-CI [-1.93, -0.18], I2: 30.3%; externalizing behavior: badjusted= -2.12, 95%-CI [-2.78, -1.47], I2: 0.0%). No association was observed between sleep duration and subsequent verbal or non-verbal intelligence Conclusion: Longer sleep duration in early preschool age (» 3.5 years of age) was associated with subsequent lower internalizing and externalizing behavior scores (» 5 years of age), but not with verbal or non-verbal intelligence. Adequate sleep duration at an early age is important for children's later mental health. Support (If Any): KG was granted a LifeCycle fellowship.